The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3311/ppci.8171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fly Ash on Properties of Self-Compacting High Strength Lightweight Concrete

Abstract: IntroductionAs known, self-compacting concrete (SCC) is highly flowable, non-segregating concrete that can spread into place, fill the formwork, and encapsulate the reinforcement without any mechanical consolidation. It doesn't require any vibration for compaction and can flow through narrow spaces without segregation and excessive bleeding [1]. Therefore SCC is one of the greatest innovations of concrete technology. It was introduced in construction industry in early 1990s. Similar to the normal vibrated conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 19 publications
1
11
0
2
Order By: Relevance
“…A study from Mushtaq et al [6] was also found the presence of fly ash increased the mechanical properties including compressive, split tensile and flexural strengths off SCC mixtures. The similar study was also reported by Iqbal et al [7] Based on some previous experimental works, this study aims to investigate the effect of different fineness of fly ash sourced from PLTU II North Sulawesi in Amurang. It is expected that finer particles could improve the workability of SCC mixtures based on slump-flow and L-box tests and also contribute the mechanical properties of concrete containing fly ash.…”
Section: Introductionsupporting
confidence: 64%
“…A study from Mushtaq et al [6] was also found the presence of fly ash increased the mechanical properties including compressive, split tensile and flexural strengths off SCC mixtures. The similar study was also reported by Iqbal et al [7] Based on some previous experimental works, this study aims to investigate the effect of different fineness of fly ash sourced from PLTU II North Sulawesi in Amurang. It is expected that finer particles could improve the workability of SCC mixtures based on slump-flow and L-box tests and also contribute the mechanical properties of concrete containing fly ash.…”
Section: Introductionsupporting
confidence: 64%
“…The overuse of natural aggregate in the construction sector has harmed the environment in recent decades, and it is estimated that about 7.5 billion tonnes of aggregates are annually consumed by the concrete industry [1][2][3][4][5]. This environmental issue can be somewhat solved by partial replacement of natural aggregates with artificial lightweight aggregates in the building process [6][7][8][9][10]. Although the use of lightweight concrete (LC) dates back to the Roman Empire, modern age artificial lightweight aggregates were produced in the middle of the 20 th century and then they were developed by researchers in the concrete industry [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…La mezcla de CAC con ceniza volante [38] indica que el reemplazo de OPC por FA generó un mayor flujo de asentamiento (2,54 % y 2,83 % para los CAC con 35% y 50% de FA respectivamente), menor tiempo en el embudo en V y una relación H2/H1 mayor en comparación con su mezcla de referencia (CAC 100_FA-0), este comportamiento es característico de algunos FA en CAC [43]. También, el uso de FA hizo que el contenido de superplastificante (SP) disminuyera en las mezclas de CAC, comportamiento que coincide con el obtenido en el estudio realizado por Gesoglu et al,…”
Section: Resultados De Ensayos En Estado Frescounclassified